Attitude to multiculturality at school scale: validation and psychometric properties on a Chilean sample - Mera Lemp, María José (2021)
The increasing number of immigrant students on the Chilean educational system stresses the importance of study teachers’ attitudes to multiculturality in schools settings. Nevertheless, there is a lack of adequate measurement instruments to apply on Chilean population. The aim of this work was to validate the Attitude to Multiculturality at School Scale (León del Barco et al., 2007) on a Chilean sample, composed by N=160 teachers. Confirmatory factor analysis showed that the unifactorial model had the best fit to the data. Correlation analysis revealed significant relations between attitude to multiculturality at school, perceived out-group threat and prejudice. Linear regression analysis showed that perceived threat and prejudice explained 42% of the attitude to multiculturality at school variability, supporting criterion validity.